Potential use of olive stone biochar as a hydroponic growing medium - Karakas, Ceren; Ozcimen, Didem; Inan, Benan (ELSEVIER, 2017)
In this study, biochar production from olive stone was carried out under different conditions and effects of temperature, nitrogen gas flow and heating rate on yield of biochar were investigated. The highest biochar yield was obtained under the carbonization temperature of 773 K, heating rate of 5 K/min and nitrogen gas flow of 500 ml/min. Characterization of biochar was performed with FTIR, TGA, SEM and BET analysis. In order to investigate the potential use of biochar in hydroponic system as solid media, it was evaluated for cultivating tomato seedling, and a comparison between using biochar and other materials such as perlite and coco peat for hydroponic growth was presented. Experimental study showed that the tallest tomato seedling was achieved with the media includes olive stone biochar. In conclusion, olive stone biochar can be used as effective solid media material for soilless agriculture methods like hydroponic system.
Keywords: Biomass; Olive stone; Biochar; Carbonization; Soilless agriculture; Hydroponic; PYROLYSIS TEMPERATURE; HEATING RATE; NITROGEN; CHARS; Chemistry; Energy & Fuels; Engineering